The researcher documentalist in a specialized TV program. Work process and sources management in ‘This is Art’ - Lillo, Sonia; Guallar, Javier (Cuadernos de Documentación Multimedia, 2019)
The professional profile of the documentalist researcher in television productions is presented from the case study of his participation in the television program This is art. The documentalist’s work is analyzed in each of the work phases of the program, following a chronological order of action and fundamental aspects of the researcher’s work are studied, such as the use of information sources and the copyright management.
Keywords: Television; Audiovisual documentation; Professional profiles; Documentalists; Researchers; Information sources; Specialized sources; Copyright; Copyright management.